The Crack Propagation in Different Rock Types: A Comparative Seismic Simulation - Mughieda, Omer; Kaiwaan, Abdulhai; Azimi, Sayed Javid; Namdar, Abdoullah; Liu, Yuyi; Alzaylaie, Marwan (Civil Engineering Journal, 2025)
The presence of a preexisting crack in a rock can affect its stability during seismic events, leading to reduced strength and stiffness. This study, which aims to examine how different types of preexisting fracture angles and the mechanical properties of the rock impact real-time cracking propagation modes and crack propagation shape, has practical implications. The researchers used ABAQUS software to apply simulated seismic loading to their model and studied crack propagation using the extended finite element method (XFEM). They found that the crack propagation shape and real-time cracking propagation vary based on the preexisting fracture angles and the mechanical properties of the rock. Additionally, they observed a significant relationship between strain leading to nonlinear deformations and the mechanical properties and fracture seismic toughness mechanism. These findings can be applied to improve the prediction of failure mechanisms in rocks with different crack shapes and could potentially enhance seismic response simulation and geotechnical earthquake engineering codes. The numerical simulation results were validated and compared to existing literature, further highlighting the practical applications of this study's findings. Doi: 10.28991/CEJ-2025-011-01-01 Full Text: PDF